Phenotype of heterozygous familial hypercholesterolemia caused by deletion of LDLR gene exons 2-10: a case report - A. M. Moiseeva; O. N. Ivanova; V. S. Emelyanchik; E. Yu. Emelyanchik; O. V. Marilovtseva; S. Yu. Nikulina; A. V. Protopopov (Российский кардиологический журнал, 2024)
Introduction. Analysis and comparison of clinical and functional characteristics of patients with familial hypercholesterolemia (FH) with molecular genetics data make it possible to clarify the disease nature and determine the management strategy taking into account the clinical and genetic status. Considering that biochemical criteria are the leading ones in the diagnosis of FH, the study of family cases complements the disease understanding.Brief description. An analysis of the genealogical and individual data, physical and general clinical examination of three family members, advanced lipid testing, and vascular ultrasound were performed. A two-stage molecular genetics study was conducted as follows: the first stage involved parallel sequencing of 60 genes associated with FH; the second stage involved DNA assessment by the multiplex ligation-dependent probe amplification method of the low-density lipoprotein receptor (LDLR) gene to identify large deletions.Discussion. Patients with deletions in LDLR gene exons 2-10 have the most severe clinical and laboratory abnormalities and early development of cardiovascular diseases. Families with FH have the highest concentration of genomic abnormalities that can lead to atherosclerosis lesions even in preschool children and may require non-standard lipid-lowering therapy, including biopharmaceuticals.